Strategies for radiology departments in handling the COVID-19 pandemic - Ashari, Muhammad Aminuddin (Diagn Interv Radiol, 2020)
The world is facing an unprecedented global pandemic in the form of the coronavirus disease 2019 (COVID-19) which has ravaged all aspects of life, especially health systems. Radiology services, in particular, are under threat of being overwhelmed by the sheer number of patients affected, unless drastic efforts are taken to contain and mitigate the spread of the virus. Proactive measures, therefore, must be taken to ensure the continuation of diagnostic and interventional support to clinicians, while minimizing the risk of nosocomial transmission among staff and other patients. This article aims to highlight several strategies to improve preparedness, readiness and response towards this pandemic, specific to the radiology department.